Human dynamics in the Southern Puna of Chile (25°-27°s) during the Late Holocene: abandonment, re-occupation and diversification - López Mendoza, Patricio; Loyola, Rodrigo; Carrasco, Carlos; Latorre, Elvira; Méndez, Víctor (Frontiers in Environmental Archaeology, 2024)
We discuss the process of human re-occupation of the Southern Puna (25°-27°S) during the Late Holocene through a variety of lines of evidence, such as ceramics, faunal bones, lithic technology, sources of raw materials like obsidian, and rock art, and their integration with spatial analyses using least-cost paths. Our results indicate a process in which niches were formed in the puna, focused on a variety of activities such as vicuña hunting; exploitation of lithic sources, minerals and pigments; camelid grazing; symbolic manifestations, and inter-Andean circulation. This suggests that human dynamics in the highlands of the Southern Puna toward the Late Holocene were motivated by a range of biotic and abiotic resources, and different modes of occupation, which tended to become diversified in the long term; nevertheless, they retained a common base in vicuña hunting and obsidian procurement, circulation and exchange.